Curriculum Integration Across Subjects in Secondary Schools Through Project-Based Learning (Sainteknol : Jurnal Sains dan Teknologi, 2022)
The 21st century is centered on the massive development of technology. Humans applied technology in almost all fields and even all activities in this era. It makes the challenges encountered by people and the general public exceedingly complicated and insufficient if only one discipline is considered. The interdisciplinary approach becomes a learning strategy that has to be enhanced. This approach promotes the study of learning on problem-solving efforts by including a review of diverse points of view from relevant or acceptable cognate science. The development of 21st-century learning using these approaches is essential to balance students' abilities with current requirements and quick changes due to science and technology's rapid progress. Various learning models can implement integration between subjects using interdisciplinary approaches, one of them is project-based learning. This study aims to describe and analyze the application of curriculum integration between subjects through student project-based activities conducted by MTs Surya Buana Malang. This research uses a case study research method and is analyzed descriptively qualitatively to see the integration project activities and their implications for students' metacognitive abilities in reviewing and finding solutions to a problem. The results showed that this activity encourages the improvement of several learning skills such as critical thinking, metacognition, problem-solving, innovation and creativity, communication and collaboration, and information literacy. In addition to successfully realizing multi-source learning, integration between subjects also helps students determine the practical value of the topics they learn to encourage the formation of a meaningful learning process.